2018
DOI: 10.1038/s41598-018-34637-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated gene expression predicts tumor aggressiveness in African-American prostate cancer patients

Abstract: Molecular mechanisms underlying the health disparity of prostate cancer (PCa) have not been fully determined. In this study, we applied bioinformatic approach to identify and validate dysregulated genes associated with tumor aggressiveness in African American (AA) compared to Caucasian American (CA) men with PCa. We retrieved and analyzed microarray data from 619 PCa patients, 412 AA and 207 CA, and we validated these genes in tumor tissues and cell lines by Real-Time PCR, Western blot, immunocytochemistry (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…In PCA tissues, NKX3.1, APPL2, TPG5, ALDH1A3, and AMD1 transcripts are significantly upregulated. Immunohistochemistry studies confirmed the overexpression of TPD52 and LTC45 in AAM compared to CaM prostate cancer [323].…”
Section: Racial Influences On Prostate Cancer Genomicsmentioning
confidence: 94%
“…In PCA tissues, NKX3.1, APPL2, TPG5, ALDH1A3, and AMD1 transcripts are significantly upregulated. Immunohistochemistry studies confirmed the overexpression of TPD52 and LTC45 in AAM compared to CaM prostate cancer [323].…”
Section: Racial Influences On Prostate Cancer Genomicsmentioning
confidence: 94%
“…E006AA cells are also available from Millipore Sigma but recent report revealed that E006AA-hT were 86% closer to renal cell carcinoma [32]. These cells were cultured as we previously described [57]. Briefly, cells were maintained in either DMEM or RPMI 1640 medium supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (Life Technologies Corp., Grand Island, NY, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…RC77T/E PCa cells and RC77N/E normal prostate cells were provided by Dr. J.S. Rhim (Uniformed Services University) and maintained as described [57]. All cells were maintained at 37 • C and 5% CO 2 and tested for mycoplasma every six months.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…It is widely known that specific mutations are able to induce cancer [4] and that many genes and microRNAs are deregulated in tumor tissues [5]. The study of the genomic characteristics of each cancer has lead to the establishment of diverse subtypes defined by the different mutations they include and with a very heterogeneous response to drugs and survival [6]. To address the differences between these subtypes, many bioinformatic approaches have been developed, such as CancerSubtypes, a R package aimed to retrieve all the main computational methods for cancer subtypes identification and analysis [7].…”
Section: Introductionmentioning
confidence: 99%